2017
DOI: 10.1213/ane.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic Antiemetics Metoclopramide and Domperidone Block Cardiac Voltage-Gated Na+ Channels

Abstract: Our data demonstrate that the clinically relevant cardiotoxicity of domperidone and metoclopramide corresponds to a rather potent and local anesthetic-like inhibition of cardiac Na channels including Nav1.5. These data suggest that Nav1.5 might be a hitherto unrecognized molecular mechanism of some cardiovascular side effects, for example, malignant arrhythmias of prokinetic and antiemetic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…On the other hand, after the one-week therapy, there were clinically related changes in the ECG of two patients of the metoclopramide group, particularly prolongation of QT intervals. In similarity to the findings of the current study, other studies and case reports have reported cardiotoxic effects caused by metoclopramide especially with higher doses and with long-term use [44,45].…”
Section: Safetysupporting
confidence: 92%
“…On the other hand, after the one-week therapy, there were clinically related changes in the ECG of two patients of the metoclopramide group, particularly prolongation of QT intervals. In similarity to the findings of the current study, other studies and case reports have reported cardiotoxic effects caused by metoclopramide especially with higher doses and with long-term use [44,45].…”
Section: Safetysupporting
confidence: 92%
“…A meta-analysis by Trelle et al 13 showed that most NSAIDs administered chronically increased morbidity and mortality in patients with cardiovascular disease. Clinically relevant cardiotoxicity is associated with the anti-emetics domperidone and metoclopramide due to their rather potent and local anaesthetic-like inhibition of cardiac sodium channels, leading to cardiovascular side effects such as malignant arrhythmias 14 . Inhibition of the hERG (human Ether-a-go-go Related Gene) channel by clozapine also results in clinically overt cardiotoxicity 15 , 16 …”
Section: Drug-induced Arrhythmiasmentioning
confidence: 99%
“…The cardiotoxic effects of metoclopramide and domperidone were investigated in neonatal rat cardiomyocytes. Cardiotoxicity was deemed to be due to potent local anesthetic-like inhibition of cardiac Na channels 94 and inhibition of hERG channel activity, which inhibits the rapid component of the cardiac delayed rectifier K (+) current. 88 , 95 Recently, a meta-analysis of observational studies reported a 70% increase in the risk of cardiac arrhythmia and sudden cardiac death with domperidone use.…”
Section: Drug–drug Interactionsmentioning
confidence: 99%